Still Waters Run Deep: Humility as a Master Virtue. Issue 4 (December 2017) - Lavelock, Caroline R.; Worthington, Everett L.; Griffin, Brandon J.; Garthe, Rachel C.; Elnasseh, Aaliah; Davis, Don E.; Hook, Joshua N.
We present two intervention studies designed to promote humility and other virtues. In Study 1, we compared the PROVE Humility workbook (Lavelock, Worthington, & Davis, 2012/2013) to alternative workbooks, each designed to promote a particular virtue (e.g., forgiveness, patience, self-control) or mood state (positivity). Participants who completed the PROVE Humility workbook reported greater increases in humility and other virtues when compared to participants in the other conditions. In Study 2, we revised the workbook and tested it against a test-retest control condition. Study 2 replicated the findings from Study 1, such that participants who completed the PROVE Humility workbook reported improvements in humility and other virtues (e.g., forgivingness and patience), as well as reductions in negative affect. These findings support the idea of humility being a master virtue, and we recommend future directions for the clinical application of humility.